Dedicated bioenergy crop impacts on soil wind erodibility and organic carbon in Kansas - Evers, Byron J.; Blanco-Canqui, Humberto; Staggenborg, Scott A.; Tatarko, John (My University, 2013)
Dedicated bioenergy crops such as perennial warm-season grasses (WSGs) may reduce soil erosion and improve soil properties while providing biomass feedstock for biofuel. We quantified impacts of perennial WSGs and row crops on soil wind erodibility parameters (erodible fraction, geometric mean diameter of dry aggregates, and aggregate stability) and soil organic carbon (SOC) concentration under a dedicated bioenergy crop experiment in eastern Kansas after 4 and 5 yr of management. Soil properties were measured under switchgrass (Panicum virgatum L.), big bluestem (Andropogon gerardii L.), miscanthus (Miscanthus × giganteus), and annual row crops including continuous corn (Zea mays L.), photoperiod sorghum [Sorghum bicolor (L.) Moench.], sweet sorghum, and grain sorghum. Perennial WSGs reduced wind erodible fraction by 1.08 to 1.16 times compared with row crops. The geometric mean diameter of dry aggregates under switchgrass and miscanthus was 2.8 to 4.5 times greater than under row crops. Dry soil aggregate stability under miscanthus and big bluestem was greater than under row crops. After 5 yr, differences in SOC concentration between WSGs and row crops were not statistically significant for the 0- to 15-cm depth. Photoperiod sensitive and sweet sorghum had greater biomass yield than WSGs. In 2011, miscanthus yielded more biomass than corn by 5.3 Mg haˉ¹. Overall, growing dedicated bioenergy crops can reduce the soil’s susceptibility to wind erosion but may not significantly increase SOC concentration in this region in the short term.
Citation: Evers, Byron J., Humberto Blanco‐Canqui, Scott A. Staggenborg, and John Tatarko. “Dedicated Bioenergy Crop Impacts on Soil Wind Erodibility and Organic Carbon in Kansas.” Agronomy Journal 105, no. 5 (2013): 1271–76. https://doi.org/10.2134/agronj2013.0072.
Keywords: Bioenergy crops; Soil erosion; Perennial warm-season grasses; Wind erodibility